Civil society engagement in multi-stakeholder dialogue: a qualitative study exploring the opinions and perceptions of MeTA members. Issue 1 (December 2017) - Buckland-Merrett, Gemma; Kilkenny, Catherine; Reed, Tim
Abstract Background The Medicines Transparency Alliance (MeTA) is an initiative that brings together all stakeholders in the medicines market to create a multi-stakeholder dialogue and improve access, availability and affordability of medicines. Key to this multi-stakeholder dialogue is the participation of Civil Society Organisations. A recent MeTA annual review, identified uneven engagement of civil society organisations in the multi-stakeholder process. This study was designed to explore the engagement of Civil Society Organisations in the MeTA multi-stakeholder process and the factors influencing their participation. Methods Participants were drawn from a convenience sample of key MeTA informants attending a MeTA global meeting in Geneva in 2014. Study participants consisted of members of MeTA, which included representatives from government, the private sector and civil society. In-depth semi-structured face-to-face interviews were conducted to identify perceptions around the barriers to civil society engagement in the multi-stakeholder process. Interviews were guided by a conceptual framework exploring the three main themes of the political environment, relative stakeholder strength and agenda setting/gatekeepers. Interviews were structured to enable additional themes to emerge and be explored. Fifteen interviews were conducted. The interviews were audio recorded, transcribed verbatim and analysed using a general inductive approach. All interviewees provided written informed consent. Results Findings were captured within three main overarching themes: the political environment, relative stakeholder strength and agenda setting/gatekeepers, with the opportunity for additional themes to emerge in the interviewing process. The study conformed these three themes were important in the engagement process. Participants reported that civil society engagement is particularly limited by those who set the agenda. It was largely seen that the political environment was the significant factor that enabled or disabled all others. The findings counter the argument that CSO barriers to engagement are predominantly due to capacity issues. Conclusions This study enriches previous findings by providing insights into civil society participation in multi-stakeholder dialogue, specifically the MeTA initiative. The development of more rigorous and systematic accountability mechanisms in order to maintain the legitimacy of decision-making processes and establish more equal power relations would significantly benefit the engagement of civil society organisations. The results inform practical recommendations for MeTA and future multi-stakeholder programmes tasked with improving policy on the access, availability and affordability of medicines.